2015
DOI: 10.1093/heapol/czu143
|View full text |Cite
|
Sign up to set email alerts
|

Mortality outcomes in hospitals with public, private not-for-profit and private for-profit ownership in Chile 2001-2010

Abstract: The question about which type of hospital ownership performs better in Chile remains open. Policy decisions regarding health service provision requires more evidence explaining differences by ownership. Better controls for health risk and hospital characteristics are suggested to address these differences in hospital performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 7 publications
0
10
0
1
Order By: Relevance
“…In the Netherlands, out of 2,363,332 hospital admissions in the years 2005-2007, 3.85% ended with death [9]. In an analysis of hospital data from Chile for the period 2001-2010 covering 16,205,314 discharges, death was reported in 3.5% of cases [6]. In our previous study we assessed in-hospital mortality in patients undergoing surgical treatment on the basis of a 4-year observation of the same general population as in the current study and found that the mean surgery-related in-hospital yearly mortality was approximately 1% [23], thus four times lower than the one for non-surgery-related deaths reported here.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the Netherlands, out of 2,363,332 hospital admissions in the years 2005-2007, 3.85% ended with death [9]. In an analysis of hospital data from Chile for the period 2001-2010 covering 16,205,314 discharges, death was reported in 3.5% of cases [6]. In our previous study we assessed in-hospital mortality in patients undergoing surgical treatment on the basis of a 4-year observation of the same general population as in the current study and found that the mean surgery-related in-hospital yearly mortality was approximately 1% [23], thus four times lower than the one for non-surgery-related deaths reported here.…”
Section: Discussionmentioning
confidence: 99%
“…There are also studies assessing mortality in specific hospital departments, mostly intensive care units [3,4]. Other studies, when analyzing large and very large populations [5][6][7][8][9][10][11], did not distinguish between surgical and non-surgical deaths or showed only surgical mortality [12]. However, there are no studies assessing non-surgical mortality in a large population (of any country) across all diseases or disease groups.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of Chile, a study shows differences in mortality by type of hospital ownership, which in turn is related to an individual’s socioeconomic characteristics, though the latter are not explicitly incorporated in the estimations. 24 Other evidence points to a non-linear relationship between income and self-perceived oral health. 25 There is also some evidence on healthcare utilisation (but not LOS), with higher utilisation for general practitioners and physician visits among richer adults, while emergency room visits and hospitalisations are concentrated among lower-income quintiles.…”
Section: Discussionmentioning
confidence: 99%
“…Dieser Unterschied resultiert wohl aus der Umstellung des Finanzierungssystems in 2003 und die Auswirkungen auf interne Prozesse. Schließlich kamen aktuelle Studien aus Österreich [22], Niederlande [23], Chile [24], Spanien [25], Schweiz [26] und Norwegen [27] auch zu unterschiedlichen Ergebnissen, weshalb keine generalisierten Aussagen hinsichtlich einer Effizienzsteigerung nach einem Trägerwechsel getroffen werden können, obwohl diese bei einer Privatisierung erhofft wird. In ▶ Tab.…”
Section: Mögliche Gründe Für Privatisierungen In Deutschland Mit Besounclassified